Hospitalité [videorecording (DVD)] - Sugino, Kiki; Sugino, Kiki; Fukada, Kōji, 1980-; Fukada, Kōji, 1980-; Yamauchi, Kenji, 1963-; Furutachi, Kanji; McCord, Will (Film Movement series, 2012)
Hospitalité: Mikio Kobayashi lives quietly with his wife, daughter, and divorced sister in downtown Tokyo, where xenophobic neighbors insist they attend community watch meetings, and the only recent excitement is the disappearance of a pet parrot. One day Kagawa appears, claiming to be the son of a financier who once helped Kobayashi's company. Kagawa soon ingratiates himself as a live-in employee and proceeds to comically turn the Kobayashi's monotonous life upside down with his odd behavior, unexpected visitors, and bizarre schemes.